2019
DOI: 10.1002/qj.3699
|View full text |Cite
|
Sign up to set email alerts
|

Linking extreme precipitation in Southeast Asia to equatorial waves

Abstract: Equatorially trapped waves, such as Kelvin Waves, Equatorial Rossby Waves and Westward‐moving Mixed Rossby–Gravity (WMRG) Waves, play a major role in organising tropical convection on synoptic to sub‐seasonal time‐scales. These waves have the potential to provide an important source of predictability for high‐impact weather in Southeast (SE) Asia and the Tropics more widely. To aid understanding of the role played in high‐impact weather by such waves, the observed statistical relationship between identified eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 57 publications
0
65
0
Order By: Relevance
“…The dominant role of Kelvin‐wave‐induced rainfall variability in Indonesia is consistent with the findings of previous studies (Lubis and Jacobi, 2015; Ferrett et al ., 2019), albeit here with a detailed regional analysis based on surface rain‐gauge data and a gridded rainfall product. This study emphasizes that the probability of extreme precipitation over Java Island increases on days when the equatorial wave wet phase is occurring.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The dominant role of Kelvin‐wave‐induced rainfall variability in Indonesia is consistent with the findings of previous studies (Lubis and Jacobi, 2015; Ferrett et al ., 2019), albeit here with a detailed regional analysis based on surface rain‐gauge data and a gridded rainfall product. This study emphasizes that the probability of extreme precipitation over Java Island increases on days when the equatorial wave wet phase is occurring.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) showed that high‐amplitude CCEWs play a significant role in enhancing daily and diurnal rainfall in Southeast Asia. However, most of the changes in rainfall intensity and extremes reported in these studies are confined over the ocean rather than the land especially Java, likely due to biases in the satellite data (see figure 4 in Ferrett et al ., 2019 and figure 5 in Sakaeda et al ., 2020). Previous studies have found that the TRMM satellite tends to underestimate torrential rainfall over land regions in Indonesia on a sub‐daily‐to‐daily time scale, owing to the inadequate detection capability of the satellite, especially during the rainy season (e.g., As‐Syakur et al ., 2011; Vernimmen et al ., 2012; Prasetia et al ., 2013; Giarno et al ., 2018; Sekaranom et al ., 2018).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations